Combination Treatment in Ulcerative Colitis using 5-Aminosalysilic Acid (5-ASA) and Polysaccharide Peptide of Indonesian Ganoderma lucidum Mycelium Extract - Simadibrata, Marcellus; Rachman, Aditya; Budimutiar, Felix; Simadibrata, Paulus; Abdullah, Murdani; Haloho, Raja Mangatur; Wijaya, Anthony Eka; Bisuk, Batara; Maharani, Shabrina; Mustikarani, Dewi; Simadibrata, Daniel Martin; Sugita, Peter (The Indonesian Society for Digestive Endoscopy, 2023)
Background: Inflammatory bowel disease (IBD) is idiopathic disease characterized by chronic inflammation of the gastrointestinal tract. Polysaccharide peptide of Ganoderma lucidum mycelium extract (PPGL) is considerably a good option for adjunctive therapy of IBD. This study aims to evaluate the benefit of PPGL in patients treated with 5-ASA.Method: A retrospective observational cohort study was conducted to examine the medical records of 124 ulcerative colitis patients. There were 80 patients in intervention group who were treated with a combination of 5-ASA and PPGL, and there were 44 patients in the control group who were treated with 5-ASA only. Clinical and laboratory endpoints were observed at the baseline and after 30, 60, and 90 days. Clinical endpoints included abdominal pain, bloody diarrhea, aphthous stomatitis, and polyarthritis; meanwhile, laboratory endpoints included hemoglobin level, ESR, CRP, fecal calprotectin, M2-pyruvate kinase (MP2K), fecal culture, C. difficile culture, and colonoscopy results. Clinical trials conducted after patient enrollment with registry number ClinicalTrials.gov NCT04029649.Results: On day-30 there was a significant difference between intervention group 45.6% and control group 2.3% in abdominal pain complaints (p 0.001). Moreover, laboratory parameters of fecal calprotectin (p 0.001), fecal MP2K (p = 0.015), and hemoglobin (p 0.001) were considerably better in intervention group on day-30. These differences were consistently found on day 60 and 90.Conclusion: The study implies potential correlation between PPGL administration and improvement of clinical and laboratory endpoints up to 90 days. A larger randomized, blinded, prospective study is required to confirm these effects in ulcerative colitis.